THE CONDITION OF PLYWOOD INDUSTRIAL WORKERS : A CASE STUDY IN SUMBEREJO, CENTRAL JAVA - Nurdien H. Kistanto (JOURNAL OF COASTAL DEVELOPMENT, 1997)
Java is often seen as epitomizing a subsistence farming economy, but since the establishment of sugar factories in the first half of the nineteenth century Javanese villages have been familiar with the notion of factory work and factory workers. As a result of establishment of many large-scale factories in the 1970s, the industrial workforce in java has grown rapidly. These factories from part of the large-scale modern manufacturing and processing sector of the economy which is expected to absorb more manpower as the Indonesian economy is transformed with the enlargement of its industrial base. As a consequence of increasing population in rural Java, structural changes will continue: agriculture will continue to decline, while manufacturing, trade and services will have to play an increasingly important role in absorbing new entrants into the workforce. Limitations on employment in agriculture force people to join the manufacturing workforce : labour will be “pushed” into manufacturing, trade and service, rather than “pulled” out of agriculture (to use White’s description). In Sumberejo, the industrialized village under study, the implications of such a view can be seen in the context of absorption of new entrants into the plywood manufacturing workface. Based on a field research, it goes to the analysis of conditions of industrial worker in the rural village where the plywood factory has been established since the late 1970s. one indication is clear that an ongoing process of diversification of rural-farm occupational opportunities has been taking place; it is also obvious that there is a considerable decrease in rural farm occupational opportunities. Moreover, increasing pressure on land, both fragmentation through inheritance and alteration for industry, has forced a growing number of villages, particularly the younger and more educated but landless, to seek employment off the farm, which is in Sumberejo in the form of plywood manufacturing workforce. The field  survey and observation reveal that a considerable number of plywood factory worker, or their household members, in Sumberejo seek additional income for their households. Those who seek other incomes are not only they who earn a smaller income form the factory; some non-staff members of the factory with comparatively larger industrial income, and/or their wives and other household members, have additional incomes from non-industrial activities, such as farming and trading. Without additional incomes from other activities, many of them can hardly improve their modest lives.